Cellulolytic and lignolytic enzyme activity by different strains of Humicola insolens on six different compost formulation at different pH - PATHAK, ASHUTOSH (Mushroom Research, 2018)
In present investigation extracellular secretion of cellulolytic and lignolytic enzymes of four different strains of H. insolens were assayed on six different compost formulations at different pH and highest cellulolytic and lignolytic activity was exhibited in formulation-6 (F-6) in terms of xylanase and CMCase having wheat bran in medium followed by formulation-5 and 2 (F-5 and F-2) having cotton seed meal and cotton seed cake. Highest laccase activity was observed in medium supplemented with nitrogen compounds viz Cotton seed meal and cotton seed cake (F-5 and F-2) from strain-1 followed by strain-2 and 3. Least activity was observed in strain-4. Thus, from study it was concluded that formulation (F-6) containing wheat bran supported maximum liberation of these enzymes of strain-1. Therefore strain-1 of the test fungus along with formulation F-6 will be chosen best for composting. Keywords: Humicola insolens, compostimg, cellulase, laccase